2019
DOI: 10.1093/ajcn/nqz144
|View full text |Cite
|
Sign up to set email alerts
|

Persistent low body weight in humans is associated with higher mitochondrial activity in white adipose tissue

Abstract: Background Constitutional thinness (CT) is a state of low but stable body weight (BMI ≤18 kg/m2). CT subjects have normal-range hormonal profiles and food intake but exhibit resistance to weight gain despite living in the modern world's obesogenic environment. Objective The goal of this study is to identify molecular mechanisms underlying this protective phenotype against weight gain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…We next asked whether increased sympathetic tone to the adipose tissue also exists in constitutionally thin humans. We took advantage of the availability of fat tissue samples from a previously described clinical study on 30 well-characterized constitutionally thin individuals (Ling et al, 2019). Paralleling our findings in mice, we indeed found markedly increased NE levels in the WAT of constitutionally thin subjects compared to their age-and sex-matched controls (Figure 6B).…”
Section: Genetic Deletion Of Alk Increases Energy Expenditure and Confers Resistance To Obesitysupporting
confidence: 80%
“…We next asked whether increased sympathetic tone to the adipose tissue also exists in constitutionally thin humans. We took advantage of the availability of fat tissue samples from a previously described clinical study on 30 well-characterized constitutionally thin individuals (Ling et al, 2019). Paralleling our findings in mice, we indeed found markedly increased NE levels in the WAT of constitutionally thin subjects compared to their age-and sex-matched controls (Figure 6B).…”
Section: Genetic Deletion Of Alk Increases Energy Expenditure and Confers Resistance To Obesitysupporting
confidence: 80%
“…This phenotype has been termed persistent thinness [38] or constitutional thinness [39] and is defined by a body mass index of �17.5 kg/m 2 but being otherwise healthy. One intriguing characteristic of these individuals is their desire to gain weight and their self-reported difficulties in doing so [39,40]. Interpreting this phenotype in light of the dual-intervention point model, it can be rationalized that the upper intervention point in constitutionally lean subjects must be under narrow biological control and that the homeostatic defense mechanisms against fatness are engaged even upon very small increases in adipose mass.…”
Section: Why Are We Not All Obese? Evolutionary and Environmental Permentioning
confidence: 99%
“…We would like here to thank Dr Maffetone for his encouraging and constructive comment and collectively agree that body fat is a highly important criterion to consider in CT, especially given the recent study that showed smaller adipocytes but higher mitochondrial respiratory capacities in adipose tissue of CT participants (3) . Our systematic review, which exclusively focused on the inclusion criteria used in available publications, identified only two studies that considered body fat percentage in their inclusion criteriaenrolling participants with a body fat below 20 %.…”
mentioning
confidence: 73%
“…Our conclusions and the constructive comment from Dr Maffetone call for further physiological and functional investigations of both adipose and muscle tissues in individuals with CT, to better understand and diagnose this condition and hopefully propose appropriate and effective intervention strategies favouring weight gain in this population. Mélina Bailly 1,2 , Natacha Germain 2,3 , Bogdan Galusca 2,3 , Daniel Courteix 1 , David Thivel 1 and Julien Verney 1…”
mentioning
confidence: 99%